The Effect of Online Learning on Increasing Student GPA and Increasing The Quality of Graduates In Higher Education - Lukito, Hendra; Yulihasri; Al Rafni (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Online learning methods are increasingly being used, including for conducting university learning. It becomes a condition that must be avoided as part of the health protocol (hence: Prokes). Several factors influence student achievement using this online learning method, namely: student GPA, gender, ethnicity, first-generation status, and income status. The independent variables are discipline, environment, learning motivation, and learning media, while the dependent variable is GPA and the quality of graduates. The method of collecting data in this research is by distributing questionnaires to 153 student respondents. The research approach used is correlation investigation to find the relationship between variables. The method of collecting data on the sample is probability sampling, which uses a simple random sampling technique and SmartPLS software. PLS analysis using the inner model, outer model, and hypothesis testing. This study has four hypotheses. Three of them are supported, and one is not supported. The results of this study indicate a positive and significant relationship between discipline, environment, and learning motivation on GPA and graduate quality. However, the learning media variable has no relationship to the GPA variable. This research focuses on active students in the Department of Management at Andalas University and Padang State University.